Analysis of the Taxonomy, Synteny, and Virulence Factors for Soft Rot Pathogen Pectobacterium aroidearum in Amorphophallus konjac Using Comparative Genomics - Zhang, Yanan; Chu, Honglong; Yu, Liqiong; He, Fei; Gao, Yong; Tang, Lizhou (Frontiers in Microbiology, 2022)
Bacterial soft rot is a devastating disease for a wide range of crops, vegetables, and ornamental plants including konjac (Amorphophallus konjac). However, the pangenome and genomic plasticity of the konjac soft rot pathogens is little explored. In this study, we reported the complete genome sequences of 11 bacterial isolates that can cause typical soft rot symptoms in konjac by in vitro and in vivo pathogenicity tests. Based on in silico DNA–DNA hybridization, average nucleotide identity and phylogenomic analysis, all 11 isolates were determined to be Pectobacterium aroidearum. In addition, synteny analysis of these genomes revealed considerable chromosomal inversions, one of which is triggered by homologous recombination of ribose operon. Pangenome analysis and COG enrichment analysis showed that the pangenome of P. aroidearum is open and that accessory genes are enriched in replication, recombination, and repair. Variations in type IV secretion system and type VI secretion system were found, while plant cell wall degrading enzymes were conserved. Furthermore, sequence analyses also provided evidence for the presence of a type V secretion system in Pectobacterium. These findings advance our understanding of the pathogenicity determinants, genomic plasticity, and evolution of P. aroidearum.